Exploring Recent Issues on Cross-cultural Marriage towards Globalizing - Nurshahrizleen Ramlan, Sayang; Maizura Abd Rashid, Intan; Ahmad Fauzi Wan Husain, Wan; Hanie Abu Samah, Irza (International Journal of Psychosocial Rehabilitation, 2020)
The discoveries of this study have profited the field of intercultural correspondence, members, and the mentoring field. This study affirmed that a wide range of relational unions incorporate conflict. Intercultural life partners have the chance to manage struggle valuably or destructively. Because of the intricate marvel of intercultural relational unions, socially different life partners may have extra difficulties as they experience strife. These difficulties are essentially because of language familiarity, high-setting versus low-setting correspondence, and family restriction. The world is an intriguing and different place to live in. An intercultural marriage is an association of two individuals including various societies and foundations. At the point when two different societies consolidate together, there might be critical difficulties they need to confront. Each race guarantees their claim to culture. A culture may vary, starting with one and then onto the next, due to socially transmitted personal conduct standards, expressions, convictions, organizations, and every single other result of human work and thought.